Activation of extracellular regulated kinase and mechanistic target of rapamycin pathway in focal cortical dysplasia. Issue 2 (18th September 2015) - Patil, Vinit V.; Guzman, Miguel; Carter, Angela N.; Rathore, Geetanjali; Yoshor, Daniel; Curry, Daniel; Wilfong, Angus; Agadi, Satish; Swann, John W.; Adesina, Adekunle M.; Bhattacharjee, Meenakshi B.; Anderson, Anne E.
Abstract : Neuropathology of resected brain tissue has revealed an association of focal cortical dysplasia (FCD) with drug‐resistant epilepsy (DRE). Recent studies have shown that the mechanistic target of rapamycin (mTOR) pathway is hyperactivated in FCD as evidenced by increased phosphorylation of the ribosomal protein S6 (S6) at serine 240/244 (S 240/244 ), a downstream target of mTOR. Moreover, extracellular regulated kinase (ERK) has been shown to phosphorylate S6 at serine 235/236 (S 235/236 ) and tuberous sclerosis complex 2 (TSC2) at serine 664 (S 664 ) leading to hyperactive mTOR signaling. We evaluated ERK phosphorylation of S6 and TSC2 in two types of FCD (FCD I and FCD II) as a candidate mechanism contributing to mTOR pathway dysregulation. Tissue samples from patients with tuberous sclerosis (TS) served as a positive control. Immunostaining for phospho‐S6 (pS6 240/244 and pS6 235/236 ), phospho‐ERK (pERK), and phospho‐TSC2 (pTSC2) was performed on resected brain tissue with FCD and TS. We found increased pS6 240/244 and pS6 235/236 staining in FCD I, FCD II and TS compared to normal‐appearing tissue, while pERK and pTSC2 staining was increased only in FCD IIb and TS tissue. Our results suggest that both the ERK and mTOR pathways are dysregulated in FCD and TS; however, the signaling alterations are different for FCD I as compared to FCD II and TS.